How much to make and how much to buy? An analysis of optimal plural sourcing strategies - Puranam, Phanish; Gulati, Ranjay; Bhattacharya, Sourav (Strategic Management Journal, 2013)
While many theories of the firm seek to explain when firms make rather than buy, in practice firms often make and buy the same input—they engage in plural sourcing. We argue that explaining the mix of external procurement and internal sourcing for the same input requires a consideration of complementarities across and constraints within modes of procurement. We create analytical foundations for making empirical predictions about when plural sourcing is likely to be optimal and why the optimal mix of internal and external sourcing may vary across situations. Our framework also proves useful for assessing the possible estimation biases in transaction level make‐or‐buy studies arising from ignoring complementarities and constraints . Copyright © 2013 John Wiley & Sons, Ltd.